STIMULATING YOUNG LEARNERS; PHOTOGRAPHIC MEMORY THROUGH 4D FLASHCARDS TO STRENGTHEN THEIR RIGHT HEMISPHERE - Andry Azhari (LINGUA LITERA : journal of english linguistics and literature, 2022)
Abstract This research aimed to explain how stimulating young learners’ Photographic Memory through 4D flashcards can strengthen the students’ right hemisphere. In every step of human development, there area number of experiences happened that can not be just forgotten. In that process, brain characters process a number of activities. Giving the right stimulus at an early stage of age gives a very great impact on the next human development process. There are several methods that we can apply for balancing the right hemisphere capability, one of them by using flashcards as a medium that uses a card game. Flashcard hasseveral types but one of the most interesting cards is the 4D flashcard. 4D Flashcard is a card with pictures that can move and produce a sound. By introducing this Flashcard to children, they can be more excited to learn. 4D flashcard was first introduced by an application in the Smartphone called Octagon 4D Flashcard. Introducing the learning materials through 4D Flashcard can be delivered in a simple way and most important in a pleasant atmosphere both for the children and the teacher or parent. Even though the learning procedure only takes a few minutes but it gives a real benefit for children in stimulating their brain development. This research is a three-circled case study research in which applied to young English Learners in LIA Padang. The techniques were successful to improve their right hemisphere